Pengaruh Partisipasi Masyarakat dalam Pembangunan di Desa Timoreng Panua Kecamatan Panca Rijang Kabupaten Sidenreng Rappang - Suriati Suriati (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
Abstract This research was held at Timoreng Panua’s Village Office to determine the influences of people’s participation on Timoreng Panua’s development, along with the influencing factors. The data collection methods used were field observation, literature study, and questionnaire. There were forty (40) people in population, all accounted as research’s sample. The results were as followed; people’s attendance in development plan conference was 80% less good; people’s involvement on development directing process in the conference was 60% good; people’s responsibility in the act of development was 60% good; people’s involvement in taking advantage of development results was 77,50% good; people’s active involvement in decision making, planning throughout monitoring, and evaluating development process, was 50% good; the executive committee’s tasks in the development plan conference were 82,50% effective; the mechanism of conference implementation was 72,50% good; the conference participants’ participation was 67,50% less participated; the conference participants’ suggestions were 77,50% accepted; implementation of the development’s plan was 82,50% good; availability of the conference’s informant was 75% available; in the process of decision making was 82,50% good; and the conference participants’s rights in decision making was 75% notified. In term of influencing factors, there were supporting factors as followed; village officials (in term of human resources) in competency to implement the conference’s results were 87,50% competent; the existence of coordination and transparency in term of funding sources and development plans was 75% supportive. While the resisting factors came from physical environment, social-economic, and cultural factors, were indeed influencing by 75%.